(untitled) (Journal of the College of Basic Education, 2023)
Aesthetic behavior and its relationship to emotional intelligence among the students of the college of Fine Arts, Baghdad UniversityThe process of responding to stimuli aesthetic of State in situations where the relations aesthetic at a high level can move her conscience pleasure and satisfaction whether those effects pretty fairly and as far as, at the same timecensure ugliness and profile whether these effects are ugly relatively and as far as Could be considered subject to the aesthetic as an exciting and provoke the attention of the recipient makes it rushes to respond to a particular behavior iscalled the aesthetic behavior, behavior that is intentional or unintentional, the result of raising the attention of the receiver to make it aware of aesthetic values.Aesthetic response and psychological state have a distinct identity and uniquenature, a phenomenon on the table for the study, and measurable.Perhaps the most important focus of specialists in aesthetic behavior is theemotional dimension that plays a key role in shaping the kind of intelligence in which the man accepts or rejects what is offered or exposed by him are modelsof taste, calendar, known as emotional intelligence.And through the literature to inform the researcher on the psychologyfound that there is almost a consensus among specialists that the study of public behavior, they need to begin the study of intelligence as a key variable directsand drives the behavior and on the way and can distinguish the behavior of eachrecipient from the other. Specifically aesthetic behavior. Based on this, the researcher in this research tries to explore the relationship between behavior andaesthetic emotional intelligence through the implementation of two measureswere adopted from previous studies on a sample of students from the Faculty of Fine Arts, which resulted in a positive correlation between these two variablesup to the research sampl